Paradigma Masyarakat Kabupaten Siak terhadap Gerakan Politik Fundamentalis Hindu - Rohinur Annasari Harahap; Indra Harahap (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Fundamentalism is a phenomenon that appears in every religious tradition in the world such as Christianity, Judaism, Islam, Hinduism and Buddhism. Fundamentalism has played an important role in global politics, especially in its interaction with democracy in several countries. Fundamentalism appears based on several factors not only related to religious issues but also social and political issues. This study examines how the people of Siak Regency view Hindu fundamentalist political movements. This study uses a descriptive-interpretative approach.